Best Answer

Related Post

Spread the word

Digg this post

Bookmark to delicious

Stumble the post

Add to your technorati favourite

Subscribes to this post

2 Comments Already

Sam Said,
February 5th, 2011 @6:45 pm  

Go here and click on show steps:

I think wolframalpha is better than maple :)

Fazaldin A Said,
February 5th, 2011 @6:56 pm  

c = x^2 + 4x + 13 + y^2 + 6y.

making the quadratic in y, we get,

y^2 + 6y + (x^2 +4x -c +13) = 0

Solving by quadratic, we get,

y = -3 ± sqrt(-x^2 -4x -4 + c) >=================< ANSWER

Leave Your Comments Below

Please Note: All comments will be hand modified by our authors so any unsuitable comments will be removed and you comments will be appreared after approved